The Treatment of Chronic Constipation in Adults: A Systematic Review - Tramonte, Sharon M (Blackwell Science Inc, 1997)
OBJECTIVE: To evaluate whether laxatives and fiber therapies improve symptoms and bowel movement frequency in adults with chronic constipation. DATA SOURCES: English language studies were identified from computerized MEDLINE (1966 –1995), Biological Abstracts (1990 –1995), and Micromedex searches; bibliographies; textbooks; laxative manufacturers; and experts. STUDY SELECTION: Randomized trials of laxative or fiber therapies lasting more than 1 week that evaluated clinical outcomes in adults with chronic constipation. MEASUREMENTS AND MAIN RESULTS: Two independent reviewers appraised each trial's characteristics including methodologic quality. There were 36 trials involving 1,815 persons from a variety of settings including clinics, hospitals and nursing homes. Twenty-three trials were 1 month or less in duration. Several laxative and fiber preparations were evaluated. Twenty trials had a placebo, usual care, or discontinuation of laxative control group, and 16 directly compared different agents. Laxatives and fiber increased bowel movement frequency by an overall weighted average of 1.4 (95% confidence interval [CI] 1.1–1.8) bowel movements per week. Fiber and bulk laxatives decreased abdominal pain and improved stool consistency compared with placebo. Most nonbulk laxative data concerning abdominal pain and stool consistency were inconclusive, though cisapride, lactulose, and lactitol improved consistency. Data concerning superiority of various treatments were inconclusive. No severe side effects for any of the therapies were reported. CONCLUSIONS: Both fiber and laxatives modestly improved bowel movement frequency in adults with chronic constipation. There was inadequate evidence to establish whether fiber was superior to laxatives or one laxative class was superior to another.